(untitled) (Academia Journal of Medicine, 2020)
Background: In the past, the left atrial appendage (LAA) has been considered to be a relatively insignificant portion of cardiac anatomy. It is now recognized that it is a structure with important pathological associations. First, thrombus has a predilection to form within the LAA in patients with non-valvar atrial fibrillation and to a lesser extent in those with mitral valve disease (both in atrial fibrillation and in sinus rhythm). Second, the use of transoesophageal echocardiography has made clear imaging of the LAA possible, so that its size, shape, flow pattern, and content can be assessed in health and disease. Subjects and Methods: This study population consisted of 40 patients with symptomatic mitral stenosis who underwent percutaneous mitral balloon valvotomy in the cardiology department of GSL medical college, Rajahmundry over a time period of 1 April 2017 to 30 March2018. Patients in all age groups, with evidence of severe MS (MVA<1.0cm2) admitted in our institution, in whom PBMV was feasible were included. Those who were fulfilling the PBMV intervention criteria and those who had good results only were included. Results: Left atrial appendage late emptying velocity, LAALF: Left atrial appendage late filling velocity Spontaneous echocontrast (SEC) was present in 10 of the 40 patients before a procedure but completely disappeared (6 patients) or decreased (4 patients) after the procedure. LAALE & LAALF velocities measured by Doppler were increased significantly after PBMV and at 6 months follow up compared with baseline (P <0.001). Conclusion: Successful Percutaneous balloon mitral valvotomy decreases the intensity of spontaneous LA contrast, reduces the size of the LA, and improves LA and LAA function. Relief of MS may confer not only hemodynamic benefits for improvement of symptoms but also have a favorable influence on future thromboembolism.